THE INFORMAL ECONOMY AND ITS ROLE IN REDUCING THE UNEMPLOYMENT RATE IN IRAQ FOR THE PERIOD (2000-2020) - Lect. Ali Abdulkadhim Dadoosh (Scholar Express Journals, 2022)
The unorganized sector is one of the most prominent sectors that work to employ (skilled and unskilled) manpower, given that the work mechanism within this sector is not subject to the procedures of education, learning, certificates and other things typical in the labor market and that workers in this sector do not pay taxes and are not considered They are registered with the state among the unemployed, and various goods and services are available within this sector and in all fields and specialties. Therefore, they stimulate the process of economic growth for the related societies. The informal economy appeared in Iraq as a result of the state imposing restrictions on various economic transactions, especially with regard to taxes and fees. This deepened the difficulty of individuals obtaining a work contract that guarantees them a decent living. The unorganized sector is one of the most prominent sectors that work to employ (skilled and unskilled) manpower, given that the work mechanism within this sector is not subject to the procedures of education, learning, certificates and other things typical in the labor market and that workers in this sector do not pay taxes and are not considered They are registered with the state among the unemployed, and various goods and services are available within this sector and in all fields and specialties. Therefore, they stimulate the process of economic growth for the related societies. The informal economy appeared in Iraq as a result of the state imposing restrictions on various economic transactions, especially with regard to taxes and fees. This deepened the difficulty of individuals obtaining a work contract that guarantees them a decent living.
Keywords: informal economy; methods of measuring the informal economy; unemployment rate in Iraq; liquid cash flows